RESEARCH SOME BIOLOGCAL ALKALOIDS OF CATHARANTHUS ROCEUS L. IN CONDITION IN VITRO CULTURES - Minh, Nguyễn Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARY Callus regenerated conveniently from leaf segment of Catharanthus roseus L. on medium containing the combination of 2,4-D (1.0 mg l-1) and BA 0.5 mg l-1. They were solid, dry and developed on the surface of segment. The callus derived from leaf libe parenchyma. The four – week callus regenerated into shoot after three weeks of culturing on MS medium supplemented with NAA 0.5 mg l-1; BA 2.0 mg l-1. It took three weeks for the callus cultured on MS supplemented with NAA 1.0 mg l-1 to regenerate into root. There was cell suspension formation after three weeks of shake culture of callus on liquid MS supplemented with 2,4-D 0.5 mg l-1 and BA 0.5 mg l-1. The cells in suspension proliferated conveniently with cells of same size gathering into clusters of 5 – 7 cells. The present of some main alkaloids of Catharanthus roseus L., especially vinblastine in the extraction from in vitro cultures including shoots, roots and calluses was confirmed using Thin Layer Chromatography (TLC) and qualitative test using indicator reagents. Key words: vinblastine, callus, cell suspention